Synaptotagmin-1 serves as a primary Zn2+ sensor to mediate spontaneous neurotransmitter release under pathological conditions - Yijuan Xiang; Lele Cui; Jingyu Yao; Xiaochu Lou; Mengdan Wu; Jingxiao Huo; Jiaqi Fan; Hao Li; KaiYu Li; Xiaodong Wang; Yeon-kyun Shin; Xiaofei Yang; et al. (Nature Communications)
Abstract In the pre-synapse, vesicle fusion is a crucial process for neurotransmitter release in the nervous system. Under physiological conditions, synaptotagmin-1 (Syt1) locks synaptic vesicles in a priming state, allowing them to undergo synchronized neurotransmitter release upon Ca2+ activation. Elevation of intracellular ions during diseases or injuries may lead to uncontrolled neurotransmitter release independent on Ca2+ influx. However, its underlying molecular mechanism remains elusive. Here we show that elevation of the intracellular Zn2+ concentration leads to the increased frequency of spontaneous neurotransmitter release in hippocampal neurons. In the reconstituted system with neuronal SNAREs and Syt1, Zn2+ markedly enhances the fusion efficiency of liposomes via its binding to the interface between tandem C2 domains of Syt1. Moreover, Syt1 exhibits an elevated capacity to bind to anionic vesicles in the context of interaction with Zn2+, which leads to an augmentation in vesicles docking within the synaptic active zone. Finally, the mutation of the tentative Zn2+-binding site (Syt1_3M) results in a loss of activation function in spontaneous release by Zn2+, while disruption of the primary interface and the polybasic region show negligible impact on the modulatory action of Zn2+. Thus, these findings suggest that with Zn2+, Syt1 adopts an alternative regulatory mode to drive spontaneous neurotransmitter release.